2001
DOI: 10.1023/a:1010884214864
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract. Financial forecasting is an example of a signal processing problem which is challenging due to small sample sizes, high noise, non-stationarity, and non-linearity. Neural networks have been very successful in a number of signal processing applications. We discuss fundamental limitations and inherent difficulties when using neural networks for the processing of high noise, small sample size signals. We introduce a new intelligent signal processing method which addresses the difficulties. The method pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…In this section, we examine various neural network-based methods. Prediction of individual sequences in terms of time or time series prediction is challenging and at the same time an important area of study in machine learning (Giles et al, 2001;Anava et al, 2013Anava et al, , 2015Ak et al, 2015;Fang et al, 2017Fang et al, , 2020. Extracting good representative pairs of input and output data is essential in machine learning algorithms.…”
Section: Neural Network Methods For Time Series Prediction Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we examine various neural network-based methods. Prediction of individual sequences in terms of time or time series prediction is challenging and at the same time an important area of study in machine learning (Giles et al, 2001;Anava et al, 2013Anava et al, , 2015Ak et al, 2015;Fang et al, 2017Fang et al, , 2020. Extracting good representative pairs of input and output data is essential in machine learning algorithms.…”
Section: Neural Network Methods For Time Series Prediction Problemmentioning
confidence: 99%
“…Connor et al (1994) proposed a robust learning algorithm based on filtering anomalies from the data and used this filtered data for estimating parameters and do forecasting. In Giles et al (2001), they examine the difficulties of RNNs for forecasting nonstationary and noisy data, and they introduced a pre-processing method to overcome these problems. However, when the gap between the relevant information and the prediction is large, RNNs become very slow and, in some cases, are unable to learn the long-term dependencies (Bengio et al, 1994).…”
Section: Rnn Modelmentioning
confidence: 99%
“…Interestingly, to our knowledge, there has been no attempt to deploy LSTM models previously on Indian agricultural commodity exchanges to predict the spot market prices. However, LSTM has been used to predict the volatility of the S&P 500 (Xiong, Nichols, & Shen, 2015) and to forecast foreign exchange rates (Giles, Lawrence, & Tsoi, 2001). Nikou, Mansourfar, and Bagherzadeh (2019) predicted the daily close price data of a UK exchange-traded fund from January 2015 to June 2018 using four models of machine learning and indicated that the deep-learning method was better in prediction than the other methods.…”
Section: Deep-learning Modelsmentioning
confidence: 99%
“…(7). To find the optimal network configuration [44] we vary the parameters in the training, including the number of hidden layers M, the dimension of a single hidden layer N h , the number of training data N, the number of epochs and the batch size B. We did not find significant improvements in the accuracy when increasing the number of layers in the network M nor increasing the number of training data N. We calculated the MSE as a function of the dimension of the hidden layer N h and observe slight decrease with increasing N h .…”
Section: Appendix a Networkmentioning
confidence: 99%